Međunarodno pravo o klimatskim promjenama / International Law on Climate Change - Borić, Nežla (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
Climate changes are one of the most current global topics occupying an important place in the United Nations’ agenda. The devastating effects of climate changes have had a significant impact on the adoption of legally binding instruments committing Member States to enhanced engagement, especially in reducing greenhouse gas emissions and activities that will reduce global temperatures by at least two degrees. This paper analyzes legally binding documents like the United Nations Framework Convention on Climate Change, as amended by the Kyoto Protocol, and the Paris Agreement on Climate Change. Although confronted with scientific evidence of the global effects of climate change that have intensified with the development of industrial societies, states have not shown the same level of willingness to ratify and implement the said international instruments. The article suggests the need to tackle international climate law in ways that pay attention to the productive effects of these international agreements, as well as the need to examine their distributional effects, examine what new social relationships they establish and stabilize, as well as how power and power can be reorganized or rearranged by procedures which comply with international environmental law and international human rights law.